Detekcja zapachu owadów z wykorzystaniem psów w leśnictwie – innowacyjna metoda monitoringu przyrodniczego - Haidt, Andżelika; Plewa, Radosław (Leśne Prace Badawcze, 2024)
The use of dogs in scent work involves the detection of a wide range of substances, including explosives, drugs, human diseases such as cancer, diabetes and epilepsy, as well as living persons or human remains. One of the rapidly developing areas of this work is environmental scent detection using dogs, the application of which could prove important in addressing the challenges posed by the greenhouse effect and global trade. Climate change has a significant impact on forests and requires innovative solutions to protect forest ecosystems. Droughts lead to an increased occurrence of various insect pest species, especially bark beetles. In addition, global trade contributes to the spread of various invasive species. The aim of this study was to analyze the potential for the use of dogs for scent detection in forestry and for implementing this approach in Poland. Based on a literature review using specific keywords on the Web of Science and Scopus platforms, it was found that dogs can effectively detect six species (or twin species groups) of insects (Insecta), including three from the order Coleoptera – Ips typographus , Osmoderma eremita / barnabita , Anoplophora glabripennis / chinensis ; two from the order Hymenoptera – Bombus spp., Solenopsis geminata ; and one from the order Homoptera – Lycorma delicatula . Dogs specially trained to detect insect scent could serve as valuable tools in certain aspects of forest management, such as the inventory and monitoring of rare and protected species (e.g., Cucujus cinnaberinus , Boros schneideri , or Rosalia alpina ) used to designate ecologically valuable areas within the Natura 2000 network. Thanks to the availability of pheromone dispensers on the market, it is also possible to train dogs to detect wood-boring insect pests such as the invasive bark beetle Xylosandrus germanus . The use of dogs could become even more important as the protection of biodiversity is one of the European Union’s main targets for 2030 under the European Green Deal. Since environmental detection is a highly effective method, its use should be seriously considered.